El mobbing laboral y su tipicidad en la legislación ecuatoriana. - Ramírez Aguirre, Solange (2014)
In labor relations the labor mobbing is determined by labor activities tending to the worker's psychological chance, materialized by aggressive, humiliating and humiliating behavior of his superiors or co-workers whose effects are sharp and affect several areas of people's lives , With negative implications for the victim, the family, the labor organization itself and society as a whole.